Apremilast mitigates interleukin (IL)-13-induced inflammatory response and mucin production in human nasal epithelial cells (hNECs). Issue 1 (1st January 2021) - Liang, Jia; Zhuang, RuoXiao; Sun, XueYao; Zhang, Feng; Zou, Bin
ABSTRACT: Interleukin (IL)-13-associated inflammatory response is important for the pathogenesis of allergic rhinitis (AR). Apremilast is a phosphodiesterase-4 (PDE4) inhibitor approved for psoriasis treatment. Here, we investigated the potential effects of Apremilast against IL-13-induced injury in human nasal epithelial cells (hNECs). Firstly, Apremilast ameliorated oxidative stress in IL-13-challenged cells by decreasing the levels of reactive oxygen species (ROS) and the production of malondialdehyde (MDA). Secondly, Apremilast inhibited the expressions of IL-6 and IL-8. Moreover, Apremilast inhibited the expressions of the chemokines colony-stimulating factor 2 (CSF2) and chemokine ligand 11 (CCL11). Interestingly, exposure to IL-13 increased the expressions of mucin 4 and mucin 5AC (MUC5AC), which was ameliorated by treatment with Apremilast. Interestingly, we found that Apremilast inhibited the phosphorylation of c-Jun-N-terminal kinase (JNK). Importantly, Apremilast reduced the levels of c-fos and c-Jun, the two AP-1 subfamilies. The luciferase reporter assay demonstrates that Apremilast reduced the transcriptional activity of activator protein 1 (AP-1). Lastly, we found that Apremilast prevented the activation of nuclear factor kappa-B (NF-κB) by decreasing the levels of nuclear NF-κB p65 and the luciferase activity of the NF-κB reporter. In summary, we conclude that Apremilast possesses a protective effect against IL-13-induced inflammatory response and mucin production in hNECs by inhibiting the activity of AP-1 and NF-κB.